Upaya Peningkatan Efisiensi Proses Packing pada Departemen Sigaret Kretek Mesin (SKM) di PT. X - Tiffany Victoria Hendra Budiono; Herri Christian Palit (Jurnal Titra, 2022)
Efficiency is a key component of the organization, and one of the most significant areas is the production process. To support the growth of the business, PT. X has adopted the principle of continuous improvement. However, the continuous improvement projects in the production process, especially in the packing area, have not been implemented in a planned manner and have not been clearly measured. Before designing suitable improvements, the wastes that occur in the packing area must be identified. The method used in this study is Value Stream Mapping (VSM), which is a Lean Manufacturing tool for mapping the whole manufacturing process and identifying waste-producing activities. According to the findings of the analysis, the main waste that dominates the packing area is motion (95,76%), which is caused by excessive and non-ergonomic movement done by the workers in carrying out the process of moving goods. The improvement effort made is reorganizing the layout of the packing area in order to reduce existing waste. The changes made are then mapped in the future VSM. The implementation of the improvements made can reduce motion waste by 20%, production lead time by 1,27%, and worker movement distance by 12,51%.